Clinical and Psychological Factors Affecting Distress Among Chronic Warfarin Patients with Uncontrolled International Normalized Ratio - Findings and Implications (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: This study aimed to evaluate the clinical and psychological factors of distress among patients on warfarintherapy with uncontrolled International Normalized Ratio (INR) in Pakistan. Materials and Methods: Thisstudy used a convenience sampling method to achieve the target size. Perceived distress was measured usinga short version of the Cohen Perceived Stress Scale 10. The responses were recorded and statistical analysiswas conducted. Results and Discussion: Among the participants, a maximum of the participants were male(n = 280, 68.5%) compared to the females (n = 129, 31.5%). A maximum of the participants were in the above65 years category. Among all the participants, 347 patients showed the presence of low distress and 62 showedthe presence of high distress. This result indicates that there is a positive correlation between the age (P = 0.005)and duration of warfarin (P = 0.011) with distress in included patients. Associated comorbidities and history ofhospitalization showed no association with distress in the study population. Conclusion: This study reported thatwarfarin patients in Pakistan experienced a lower level of distress despite their uncontrolled INR. However, fewof the factors, such as age and duration of warfarin, were shown to be associated with the higher level of distressin the study participants.